Biomass Production and Nitrogen Accumulation by Hairy Vetch–Cereal Rye Mixtures: A Meta‐Analysis. (1st July 2018) - Thapa, Resham; Poffenbarger, Hanna; Tully, Katherine L.; Ackroyd, Victoria J.; Kramer, Matt; Mirsky, Steven B.
Abstract : Core Ideas: We reviewed aboveground biomass and total N content of hairy vetch–cereal rye mixtures vs. monocultures. Overall, mixtures produced equivalent or more biomass and N content as monoculture species. Environmental and cropping system factors affected relative productivity of mixtures. Mixtures performed better in coarse‐textured soils and following corn harvest. With increasing GDD, mixtures productivity decreases relative to hairy vetch, but increases relative to cereal rye monocultures. Agroecosystem services from cover crop mixtures are linked to aboveground biomass and total N content (kg ha −1 ). Reported values in the literature, however, vary for aboveground biomass and total N content of cover crop mixtures compared with monocultures. We conducted a meta‐analysis using results from 55 site‐years from 21 studies conducted in the United States to examine biomass and N content of hairy vetch ( Vicia villosa Roth)–cereal rye ( Secale cereale L.) mixtures compared with respective monocultures. Overall, hairy vetch–cereal rye mixtures produced 63 and 21% more biomass compared with hairy vetch and cereal rye monocultures, respectively. The N content of hairy vetch–cereal rye mixtures was 150% greater than that of cereal rye monocultures. When the proportion of hairy vetch seeds (by weight) exceeded 46% of the mixture, the mixtures accumulated equivalent or more N than the greatest yielding monocultures (usually hairy vetch). Compared with monocultures, a more consistent positive response of mixtures on biomass and N content was found on coarse‐textured soils and following corn ( Zea mays L.) rather than soybean [ Glycine max (L.) Merr.] harvest. With increasing growing degree days (GDD), the biomass and N content of mixtures decreased relative to hairy vetch monocultures but increased relative to cereal rye monocultures, suggesting better performance of hairy vetch at higher GDD. We conclude that hairy vetch–cereal rye mixtures can produce equivalent or more biomass than both monocultures and accumulate as much N as hairy vetch, and that the relative productivity of mixtures depends on soil type, previous crop, seeding proportion, and GDD.